Impact of Platelet-Rich Plasma on Bone Height Changes around Platform Switched Implants Supporting Mandibular Overdentures in Controlled Diabetic Patients - Ibraheem, Eman Mostafa Ahmed (Open Access Maced J Med Sci, 2015)
BACKGROUND: The platform switching concept was recently introduced to implant dentistry involving the reduction of restoration abutment diameter with respect to the diameter of dental implant. Long-term follow-up around these implants showed higher levels of bone preservation and proper stress distribution and improved esthetics. AIM: The aim of the present study was to evaluate the changes in bone height by means of radiographic examination around platform switched implant supporting mandibular overdentures in controlled diabetic patients. SUBJECTS AND METHODS: Fourteen male complete edentulous patients were selected and enrolled in a follow-up study plan. Split mouth technique was applied; one side implant chosen randomly with Platelet-rich-plasma (PRP) and the other without PRP, bone height changes was assessed by Cone Beam Computed Tomography (CBCT) radiographic examination after 3 months, 6 months, 9 months and 1 year later. RESULTS: There was increase in bone height loss in both sides but with no statistical significance difference between the two sides after 3 months, 6 months, 9 months and 1 year respectively. CONCLUSION: The result of this article satisfied the patients both esthetically and functionally with recorded increase in bone height loss.